Engaging within zones of proximal development on Facebook : the case of using Facebook to support learning and mentoring on a NQF Level 5 environmental education, training and development practices learnership - Chetty, Preven (Rhodes University, Faculty of Education, Department of Education, 2015)
This study focuses on two roll-outs of a, year-long National Qualification Framework (NQF) level 5, environmental education learnership in South Africa and attempts at enhancing collaborative learning at workplaces using a familiar social networking site called Facebook. This study uses the Facebook group sites created for the workplace course component of the course as one of the means of data collection. Additional interviews and focus groups with learners and administrators on both Environmental Education Training and Development Practices (EETDP) courses also informed the study. The study is located within the context of the rise of the information age, its effects on socio-ecological landscape at large and ways of using social networking sites in order to facilitate scaffolding and meaning making within zones of proximal development for environmental education learnerships. It also looks at the model of apprenticeship and workplace based learning as it is broadly located at the nexus of the SAQA-led academic inquiry into workplace based learning and professional development. It was found that the use of Facebook on the EETDP learnership allowed for collaborative learning to take place between peer to peer interactions as well as between tutors and learners. It was also noted that scaffolding processes requires both technical assistance and strong instructional input from course tutors. One of the most important findings in terms of collaborative learning and engaging within the Zone of Proximal Development (ZPD) was that learners were able to communicate more effectively and freely with both fellow learners and tutors on course after participating on the Facebook group sites. The study offers recommendations on how a social networking platform like Facebook can be utilised effectively for environmental education. The study recommends that scaffolding of workplace based tasks and concepts needs to be better integrated with the course and in both online and offline interactions between learners. It also illustrates how social networking sites can become powerful tools for creating meaning making when combined with course work.
Keywords: Social media -- Study and teaching (Higher) -- South Africa; Internet in education; Online social networks; Organizational learning; Employees -- Training of; Group work in education